Original papersPathogenic fungi in the work environment of organic and conventional farmers - Żukiewicz-Sobczak, Wioletta; Cholewa, Grażyna; Krasowska, Ewelina; Zwoliński, Jacek; Sobczak, Paweł; Zawiślak, Kazimierz; Chmielewska-Badora, Jolanta; Piątek, Jacek; Wojtyła, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Recent research conducted at the Institute of Rural Health indicated the harmfulness of organic dusts present in the environments of agricultural producers. Due to the high concentration of biological agents contained in dust grains, derived from conventional and organic cropping systems, there is a real risk of developing respiratory diseases in people doing agricultural work. Conventional and organic cropping systems differ significantly in terms of fertilization method and plant protection. Such differences may also influence the composition of biological agents in grain dust, which can cause various health effects in humans. No assessment has been carried out in farms with different systems of farming. Ambiguous statements on existing health risks in people doing agricultural work on conventional and organic farms prompted the Department of Allergy and Environmental Hazards, Institute of Rural Health in Lublin, to perform mycological tests and assess the degree of contamination with fungi pathogenic for humans in grain dust and grain from organic and conventional farms. A literature review and research conducted at the Institute of Rural Medicine show that the problem of occupational exposure to the presence of molds and mycotoxins in grains and grain dusts and their possible role in the development of pathological changes of the respiratory system is very important from the standpoint of hygiene and occupational medicine, and still requires further studies.